2016
DOI: 10.1016/j.ecolind.2015.11.056
|View full text |Cite
|
Sign up to set email alerts
|

Using assessment of net ecosystem services to promote sustainability of golf course in China

Abstract: a b s t r a c tGolf courses have been shown to have a positive impact on local biodiversity, quality of life and the economy. However, the impacts of golf courses on local environment, including ecosystem services and dis-services are not clearly understood. To explore this relationship, we took two golf courses in Beijing (a links course and a parkland course) to develop an assessment framework and present estimates of economic values of net ecosystem services, in aspects of ecosystem goods, carbon fixation, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 34 publications
1
15
0
Order By: Relevance
“…) that affect management of a golf course and in this way it is consistent with findings of Dai et al (2016), who pointed out that ecological benefits produced by golf course are higher than dis-services, in terms of financial accounting. These ecological services can also be enhanced by particular management reserved to rough areas that can play an important role in conservation of particular environments with typical plants and to improve pollination activity (Dobbs and Potter, 2016).…”
Section: Phase 3 Evaluating Alternative Solutionssupporting
confidence: 79%
“…) that affect management of a golf course and in this way it is consistent with findings of Dai et al (2016), who pointed out that ecological benefits produced by golf course are higher than dis-services, in terms of financial accounting. These ecological services can also be enhanced by particular management reserved to rough areas that can play an important role in conservation of particular environments with typical plants and to improve pollination activity (Dobbs and Potter, 2016).…”
Section: Phase 3 Evaluating Alternative Solutionssupporting
confidence: 79%
“…However, re-estimating all unit values is a heavy work, especially, considering the non-linearity in ecosystem services (Barbier et al, 2008; Koch et al, 2009) and the spatial heterogeneity of unit values (de Groot et al, 2012; Crossman et al, 2013; Drakou et al, 2015). In the primary data based approach, the difficulty for accurately valuing each individual ES is remained (Guo et al, 2001; Dai et al, 2016), although there are some technique innovations in recent years (Coscieme et al, 2014). In DVS, the OSV of an ES is determined by the TVPH and ES consumption; the OCV of an ES is determined by total ES volume, ES consumption and OSV (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In monetary ES valuation studies, there are two approaches (Jiang, 2017): (1) unit value based approach (i.e. benefit transfer) (Costanza et al, 1997; de Groot et al, 2012; Costanza et al, 2014; Kubiszewski et al, 2017) and (2) primary data based approach (Ouyang et al, 1999; Guo et al, 2001; Dai et al, 2016) (Figure 1). In non-monetary ES valuation studies, there are some biophysical approaches (Koellner and Geyer, 2013; Coscieme et al, 2014; Mancini et al, 2018), such as Emergy analysis, Ecological Footprint accounting; and some pluralistic approaches (Pascual et al, 2017; Martin and Mazzotta, 2018; Folkersen, 2018), such as the pluralistic valuation approach provided by Intergovernmental Science-Policy Platform on Biodiversity and Ecosystem Services (IPBES).…”
Section: Introductionmentioning
confidence: 99%
“…The study of golf tourism has emerged as an interesting research field [1], as very recent studies have demonstrated [14][15][16][17][18][19]. The present work tries to contribute to literature on the environmental attitudes and behaviours of golf tourists.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Correia et al [22] argued that both managers and tourists need to be aware of the importance of sustainable tourism practices. Research on sustainability in golf has increased in recent years from the perspective of golf courses [15,[23][24][25][26][27][28]. Hence, there is a substantial literature on golf courses on their negative environmental impacts, especially with respect to excessive water use [29,30], environmental pollution [31], chemical inputs [32,33], and effects on wildlife and habitat [34,35].…”
Section: Research Model and Hypotheses Testingmentioning
confidence: 99%